China–Latin America: Economic Relations in the 21st Century. Latin American Perspective on Opportunities and Threats - Ratke-Majewska, Anna (Wydawnictwo Naukowe WNPiD UAM, 2019)
This article raises the issue of China–Latin America economic relations in this century. During the first two decades of the 21st century, there has been a significant increase in trade between China and Latin America, and China’s investments in Latin America have increased. Although the presented text discusses the issues of economic cooperation, its primary objective, however, is not to present the dynamics of these relations, but to reflect on the chances and risks for Latin America resulting from economic cooperation between China and Latin America. The article thus discusses the area of opportunities and threats in numerous aspects, giving various arguments and numerous examples. The conclusions of the article refer both to emerging challenges and the prospects for cooperation.

Artykuł porusza kwestię stosunków gospodarczych Chiny–Ameryka Łacińska w tym stuleciu. W ciągu pierwszych dwóch dekad XXI wieku nastąpił znaczny wzrost handlu między Chinami i Ameryką Łacińską, a inwestycje Chin w Ameryce Łacińskiej wzrosły. Chociaż prezentowany tekst omawia kwestie współpracy gospodarczej, jego głównym celem nie jest jednak prezentacja dynamiki tych stosunków, ale refleksja nad szansami i zagrożeniami dla Ameryki Łacińskiej wynikającymi ze współpracy gospodarczej między Chinami i Ameryką Łacińską. Artykuł omawia zatem możliwości i zagrożenia w wielu aspektach, podając różne argumenty i liczne przykłady. Wnioski z tego artykułu dotyczą zarówno pojawiających się wyzwań, jak i perspektyw współpracy.
Chiny – Ameryka Łacińska: stosunki gospodarcze w XXI wieku. Perspektywa latynoamerykańska dotycząca szans i zagrożeń
Keywords: China–Latin America; economic relations; opportunities for Latin America; threats for Latin America; Chiny–Ameryka Łacińska; stosunki gospodarcze; możliwości dla Ameryki Łacińskiej; zagrożenia dla Ameryki Łacińskiej